Assessment of different insecticides for the suppression of an outbreak of Leucoptera coffeella in Jamaica - Reid, J.C; Robinson, D.E (IICA, San José (Costa Rica), 2020)
Six insecticides were evaluated for the control of Leucoptera coffeella [Perileucoptera coffeella], in a coffee plantation in Western Jamaica. Nuvacron 40 [monocrotophos], Selecron 500 EC [profenofos], Trigard 75 WP [trifluralin], Miral 500 CS [isazofos] and Miral 10 G were compared with Furadan 10 G [carbofuran]. Selecron and Miral 500 CS gave the best control resulting in 5 and 7 percent reduction, resp., in the number of mines per leaf after 6 weeks. The number of larvae per leaf was 0.9 after 1 week and 0.3 after 6 weeks in plots treated with Selecron and 0.5 after 1 week and 1.0 after 6 weeks in plots treated with Miral 500 CS. Larval mortality was 92 and 69 percent, resp., in plots treated with Selecron, and 100 and 55 percent resp., in plots treated with Miral 500 CS 1 and 6 weeks after treatment.